The effect of repeated periods of speed endurance training on performance, running economy and muscle adaptations - Skovgaard, C.; Almquist, N. W.; Bangsbo, J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The effect of repeated intense training interventions was investigated in eight trained male runners (maximum oxygen uptake (VO2-max): 59.3±3.2 ml·kg-1·min-1, mean±SD) who performed ten speed endurance training (SET; repeated 30-s `all-out` bouts) and ten aerobic moderate-intensity training sessions during two 40-day periods (P1 and P2) separated by ~80 days of habitual training. Before and after both P1 and P2, subjects completed an incremental test to exhaustion to determine VO2-max and a repeated running test at 90% vVO2-max to exhaustion (RRT) to determine short-term endurance capacity. In addition, running economy (RE) was measured at 60% vVO2-max (11.9±0.5 km·h-1) and v10-km (14.3±0.9 km·h-1), a 10-km track-running test was performed, and a biopsy from m. vastus lateralis was collected. 10-km performance and VO2-max (ml·min-1) was the same prior to P1 and P2, whereas RE was better (P<0.05) before P2 than before P1. During P1 and P2, 10-km performance (2.9 and 2.3%), VO2-max (2.1 and 2.6%) and RE (1.9 and 1.8% at 60% vVO2-max; 1.6 and 2.0% at v10-km) improved (P<0.05) to the same extent, respectively. Performance in RRT was 20% better (P<0.05) after compared to before P2, with no change in P1. No changes in muscle expression of Na+,K+-ATPase a1, a2 and ß1, NHE1, SERCA1 and SERCA2, actin and CamKII were found during neither P1 nor P2. Thus, the present study demonstrates that a second period of intense training leads to improved short-term performance and further improved RE, whereas 10-km performance and VO2-max improve to the same extent as during the first period.